Sensory acceptability of roselle leaves (Hibiscus sabdariffa) as souring agent in instant spice mix / Aladin M. Ibrahim ... [et al.] - M. Ibrahim, Aladin; Blas, Richard Daryl M.; Batobato, Maevelle Lou A.; Norcos, Christine Joy A.; Miranda, Joy Crizette S.; Sevilla, Francis G.; Baron, Davis Louie O. (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
Roselle (Hibiscus sabdariffa) leaves have been growing in popularity in terms of their use in various fields and their potential in the market. Several studies have suggested further development and evaluation of roselle leaves as an additional food source. The purpose of this study is to develop an instant spice mix using the Roselle plant as the souring agent and determine its acceptability in terms of taste, color, texture, and aroma. The study used a completely randomized design with four experimental treatments and a control. Experimental treatments were composed of varying proportions of dried roselle leaves and tamarind powder. Sixty purposely selected respondents, comprising households, food production workers, food service workers, culinary instructors, and culinary students, acted as sensory quality evaluators in the study. The study revealed that all experimental treatments were acceptable in terms of aroma, color, and texture; the taste of experimental treatments 1, 2, and 3, including the control, was rated acceptable except for treatment 4, which contained pure dried roselle leaves. This study further aims to add to the existing knowledge on the utilization, evaluation, and acceptance of roselle leaves in food production.